Pengaruh Pengangguran terhadap Kemiskinan di Provinsi Kepulauan Riau - Ria Nandika (Jurnal Archipelago, 2024)
Development aims to achieve community prosperity through economic progress by addressing various social issues, such as unemployment and poverty. In the Riau Islands Province, poverty and unemployment remain significant challenges to development. This analysis focuses on examining the correlation between the unemployment rate and poverty levels across different districts and cities within the Riau Islands Province. The analysis will provide valuable insights for evaluating regional development and will serve as input for formulating regional planning efforts related to poverty alleviation and employment. The study employs a regression analysis method, utilizing a panel data model that combines time series data (collected over a specific period for an individual) with cross-sectional data (collected over the same period for multiple individuals). The findings indicate that the open unemployment rate partially influences the poverty rate in the districts and cities of Riau Islands Province. Specifically, the unemployment rate accounts for approximately 10.7% of the variation in poverty levels, while the remaining 89.3% is attributed to other factors not examined in this model. Based on these results, recommendations suggest that addressing the issues of open unemployment and poverty should be undertaken simultaneously and synergistically, incorporating additional variables such as education and training, as well as promoting inclusive economic development. Furthermore, the government needs to enhance employment opportunities to reduce the number of unemployed and impoverished individuals in the Riau Islands Province. This can be accomplished through government programs that prioritize labor-intensive job creation and focus on poverty alleviation initiatives.